MENTORING IN NURSING EDUCATION: A SCOPING REVIEW - Yumul, Jordana Delicana; Orzal, Ma. Sofia A.; Bascos, Mark Job G. (Klabat Journal of Nursing, 2025)
Mentoring can serve as a foundation for shaping compassionate and competent nurses. While there is a growing number of studies providing evidence on the beneficial outcomes of mentoring and its integration in mentoring programs, there are few publications that synthesized the literature focusing on identifying specific mentoring strategies. The objective of this scoping review is to explore and summarize the existing literature on mentoring strategies in nursing education and its outcomes. A scoping review was conducted. The databases searched include MEDLINE, CINAHL, ERIC, ScienceDirect, and Biomed Central using the keywords “mentoring”, “nursing”, and “students” to capture all available records that included the concept of mentoring in nursing education. Studies conducted in any academic setting and areas where students conduct clinical placements, and those published in English were included. The studies were independently screened by the authors before data extraction, tabulation, and analysis. Of the 16, 450 records identified,136 articles were assessed for eligibility, and a total of 30 studies were included in the review. Five studies focused on clinical nurse-led mentoring, peer mentoring, faculty mentoring, individual and group mentoring, and tripartite mentoring. The studies consistently showed beneficial outcomes of mentoring on the personal and professional development of the students. The reviewed articles indicate that mentorship is a major strategy that significantly influences the nursing education process and various aspects therein. Mentor support provided through faculty, clinical, and peer structures enhances self-efficacy, professional identity, care, and academic success.